2001
DOI: 10.1080/02786820126857
|View full text |Cite
|
Sign up to set email alerts
|

Size Distribution Change of Titania Nano-Particle Agglomerates Generated by Gas Phase Reaction, Agglomeration, and Sintering

Abstract: In the manufacturing of nanometer-sized material particlulates by aerosol gas-to-particle conversion processes, it is important to analyze how the gas-phase chemical reaction, nucleation, agglomeration, and sintering rates control the size distribution and morphology of particles. In this study, titania particles were produced experimentally by the thermal decomposition of titanium tetraisopropoxide (TTIP) and oxidation of titanium tetrachloride (TiCl 4 ) using a laminar ow aerosol reactor. The effect of react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 32 publications
3
45
1
Order By: Relevance
“…When performing electrical mobility measurements, the classified mobility (mobility equivalent diameter, D m ) of the fractal-like aggregate is proportional to its projected area. [46,49] The results obtained from the mobility scan using the DMA and CNC showed that the geometric mean D m values of the aggregates increase with an increase in precursor evaporation temperatures. The change in precursor vapor pressure (Figure 1 a) does not result in any substantial change in the primary-particle diameters as proven by TEM.…”
Section: Particle Growth Investigationmentioning
confidence: 99%
“…When performing electrical mobility measurements, the classified mobility (mobility equivalent diameter, D m ) of the fractal-like aggregate is proportional to its projected area. [46,49] The results obtained from the mobility scan using the DMA and CNC showed that the geometric mean D m values of the aggregates increase with an increase in precursor evaporation temperatures. The change in precursor vapor pressure (Figure 1 a) does not result in any substantial change in the primary-particle diameters as proven by TEM.…”
Section: Particle Growth Investigationmentioning
confidence: 99%
“…As sintering is considered to be governed by a surface diffusion model, the characteristic time for sintering, τ, of TiO 2 particles is given by Eq. (5) (Nakaso et al, 2001). …”
Section: Iii) Sintering Of Anatase Particles (700-900°c)mentioning
confidence: 99%
“…The size of the primary particles depends on the relative rate of coalescence and collision. Initially, primary particles in combustion systems are on the order of 5-20 nm in diameter, and the primary particles are considered approximately spherical in shape (Nakaso et al 2001;Wooldridge et al 2002;Mueller et al 2009). The fractal structures are created by competition between the nucleation rate of the primary particles, the interparticle collision rate, and the coalescence or sintering rate.…”
Section: Combustion Generated Nanoparticlesmentioning
confidence: 99%